Whose body? ebook - Sayers, Dorothy L. (Peter Wimsey, 2013)
In the debut mystery in Dorothy L. Sayers’s acclaimed Lord Peter Wimsey series, the case of a dead bather draws Lord Peter into the 1st of many puzzling mysteries Lord Peter Wimsey spends his days tracking down rare books, and his nights hunting killers. Though the Great War has left his nerves frayed with shellshock, Wimsey continues to be London’s greatest sleuth—and he’s about to encounter his oddest case yet.   A strange corpse has appeared in a suburban architect’s bathroom, stark naked save for an incongruous pince-nez. When Wimsey arrives on the scene, he is confronted with a once-in-a-lifetime puzzle. The police suspect that the bathtub’s owner is the murderer, but Wimsey’s investigation quickly reveals that the case is much stranger than anyone could have predicted.   Published in 1923, during detective fiction’s Golden Age, Whose Body? introduced a character and a series that would make Dorothy L. Sayers famous. To this day, Lord Peter remains 1 of the genre’s most beloved and brilliant characters.   Whose Body? is the 1st book in the Lord Peter Wimsey Mysteries, but you may enjoy the series by reading the books in any order.   This ebook features an illustrated biography of Dorothy L. Sayers including rare images from the Marion E. Wade Center at Wheaton College.